A SOCIO LEGAL STUDY ON OUR PREPAREDNESS AND FAILURE TO TACKLE THE PROBLEMS OF HONOUR KILLING - Sharma, Gunjan; Kumar, Mandeep (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Honour crimes have been considered a difficult and misunderstood issue for centuries. The concept of respect for violence is flexible and changes according to time, place, socialization and expression. Honor crimes are defined as a behavior that affects all societies, cultures, religions and nations, manifests itself in various forms of violence, and can generally be eliminated individually or collectively. Genocide is always unjust, illegal and a serious violation of human rights. It is illegal to take someone's life without cause. This is also inappropriate and illegal. The law guarantees the right to life and dignity to every citizen. Dignity and life go together. The Constitution of India guarantees this right as a fundamental right. Life is hopeless. No one can know the next minute of life. In this case, everyone has the right and desire to live the life they want. No one should be forced to live a life where others are valued and respected. Murder is when a woman or man kills someone who does not accept the family's marriage or changes their marriage at their own will, on the grounds that it will harm the family's honor. Family law protects the family but forgets the love and compassion felt for family members.